Chemical insights into the synthetic chemistry of five-membered saturated heterocycles—a transition metal–catalyzed approach - Sunbal,; Alamzeb, Muhammad; Omer, Muhammad; Abid, Obaid-Ur-Rahman; Ullah, Mohib; Sohail, Muhammad; Ullah, Ihsan (Frontiers in Chemistry, 2023)
Drug design and delivery is primarily based on the hunt for new potent drug candidates and novel synthetic techniques. Recently, saturated heterocycles have gained enormous attention in medicinal chemistry as evidenced by the medicinal drugs listed in the FDA Orange Book. Therefore, the demand for novel saturated heterocyclic syntheses has increased tremendously. Transition metal (TM)–catalyzed reactions have remained the prime priority in heterocyclic syntheses for the last three decades. Nowadays, TM catalysis is well adorned by combining it with other techniques such as bio- and/or enzyme-catalyzed reactions, organocatalysis, or using two different metals in a single catalysis. This review highlights the recent developments of the transition metal–catalyzed synthesis of five-membered saturated heterocycles.